2005
DOI: 10.1002/cpa.20076
|View full text |Cite
|
Sign up to set email alerts
|

The generalized Dirichlet-to-Neumann map for certain nonlinear evolution PDEs

Abstract: Let q(x, t) satisfy a nonlinear integrable evolution PDE whose highest spatial derivative is of order n. An initial boundary value problem on the half-line for such a PDE is at least linearly well-posed if one prescribes initial conditions, as well as N boundary conditions at x = 0, where for n even N equals n 2 and for n odd, depending on the sign of the highest derivative, N equals either n−1 2 or n+1 2 . For example, for the nonlinear Schrödinger (NLS) and the sine-Gordon (sG), N = 1, while for the modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
127
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 103 publications
(131 citation statements)
references
References 23 publications
3
127
0
1
Order By: Relevance
“…This yields q x (0, t) in terms of a system of four nonlinear ODEs satisfied by the functions {L j ,M j } 2 1 . A further important development is presented in [9], where it is shown that it is possible to express {L j ,M j } 2 1 in terms of Φ 1 and Φ 2 . Thus the formalism presented in [9] expresses q x (0, t) in terms of a system of two nonlinear ODEs satisfied by the functions Φ 1 and Φ 2 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…This yields q x (0, t) in terms of a system of four nonlinear ODEs satisfied by the functions {L j ,M j } 2 1 . A further important development is presented in [9], where it is shown that it is possible to express {L j ,M j } 2 1 in terms of Φ 1 and Φ 2 . Thus the formalism presented in [9] expresses q x (0, t) in terms of a system of two nonlinear ODEs satisfied by the functions Φ 1 and Φ 2 .…”
Section: Introductionmentioning
confidence: 99%
“…A further important development is presented in [9], where it is shown that it is possible to express {L j ,M j } 2 1 in terms of Φ 1 and Φ 2 . Thus the formalism presented in [9] expresses q x (0, t) in terms of a system of two nonlinear ODEs satisfied by the functions Φ 1 and Φ 2 . Similarly, it is shown in [9] that the unknown boundary values for the sG, the mKdV I, and the mKdV II equations can also be expressed in terms of a system of two nonlinear ODEs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations